WILL TRADITIONAL FOOD SURVIVE THE TRENDS? INVESTIGATING LOMBOK YOUNG GENERATIONS CONSUMPTION - Yusup Apriyanto; Wan Ahmad Hasni Wan Ahmad Zulkifali (International Journal of Social Science, 2025)
This study explores the consumption patterns of traditional Sasak cuisine among Generation Z in Lombok, Indonesia, amid the influence of modern food trends. Using qualitative methods, including semi-structured interviews with eight participants aged 11–26, the research reveals a duality in food preferences. While traditional dishes like Pelecing Kangkong, Ayam pelecingan, Ayam Taliwang remain common at home due to parental influence, Gen Z increasingly favors modern, convenient, and trendy foods outside the household. Sensory preferences, time constraints, and social influences drive this shift, along with a declining interest in learning traditional cooking skills. However, many young people still express cultural pride in Sasak cuisine, suggesting opportunities for revitalization. The study highlights the need for adaptation through fusion, media promotion, and educational programs to sustain culinary heritage. Traditional food must evolve to align with Gen Z’s lifestyles, emphasizing identity, convenience, and health to remain relevant in a globalized food landscape